Implementation of the Principle of Nationalism for Indonesian Citizens Who Carry Out Mixed Marriages Without Separation of Property Related to Ownership of Land Rights in Bali Province - Hartono Hartono; Kadek Dedy Suryana; Erikson Sihotang (PT Publikasiku Academic Solution, 2025)
This research employs a normative-empirical legal research method to analyze the implementation of the principle of nationalism in land law for Indonesian citizens who enter into mixed marriages without prenuptial agreements in relation to land ownership rights in Bali Province. The empirical component involved in-depth interviews with five officials from the Regional Office of the National Land Agency (Badan Pertanahan Nasional or BPN) of Bali Province, eight notaries experienced in mixed marriage documentation, twelve legal practitioners specializing in agrarian law, and case study analysis of 25 mixed marriage property disputes processed through Bali courts from 2019 to 2024. Research objectives include analyzing the application of nationalism-based land law to Indonesian citizens in mixed marriages without property separation agreements and examining the legal consequences. The study reveals that Indonesian citizens are constitutionally entitled to land ownership rights under Article 33(3) of the 1945 Constitution. Main findings demonstrate that the principle of nationalism (grondverponding verbod) in Indonesian land law creates legal complications for mixed marriages. Indonesian citizens who acquire land rights after mixed marriage without property separation agreements face mandatory relinquishment within one year under Article 21(3) of the UUPA, or the land reverts to the state. However, Government Regulation No. 103/2015 provides solutions through court-determined property separation agreements, enabling Indonesian citizens to maintain land ownership rights while married to foreign nationals. The research concludes that urgent legal amendments are needed to balance the principle of nationalism with the constitutional rights of Indonesian citizens in mixed marriages, particularly regarding inheritance and protection of property rights.